Otimização genética de sequências de padrões de teste para circuitos VLSI. - Dias, Leonardo Alves (2016)
An integrated circuit (IC) in test mode has a higher energy consumption compared to the normal operating mode, due to the increased number of transitions in the nodes of the resulting circuit applying test patterns used to stimulate the CI during the test run resulting in high power dissipation which can damage the IC, resulting in higher costs for manufacturers. In this work we propose a genetic algorithm to optimize sequences of test patterns aiming at low energy consumption during the test run, maintaining an adequate fault coverage. It is also proposed using the Berlekamp-Massey algorithm to synthesize an integrated test patterns with low hardware sobreárea generator capable of generating sequences optimized based on Shift Register with Linear Feedback. The optimization of the sequences is done by reducing the number of transitions at nodes whose evaluation is done by a computer program developed in this study in C ++. Finally, simulations were performed with the genetic algorithm to check the behavior to optimize the number of transitions, the fault coverage and hardware sobreárea.